GJB2-RELATED NON-SYNDROMIC HEARING LOSS VARIANTS’ SPECTRUM AND THEIR FREQUENCY IN TURKISH POPULATION - Çağrı Güleç; Ayça Dilruba Aslanger; Volkan Karaman; Bernd Wollnik; Fatih Tepgeç; Hülya Kayserili Karabey; Zehra Oya Uyguner (İstanbul Tıp Fakültesi Dergisi)
Objective: Hearing loss (HL) is one of the most prevalent chronic conditions in children and has consequences in speech, language, education, and social functioning which impede the quality of life. Due to the major involvement of the genetic factors in HL, especially non-syndromic HL (NSHL), genetic diagnosis and genetic counseling have a major impact on early management of the affected individuals and their families. Herein, we report the GJB2 gene variants and their frequencies in NSHL cohort at a tertiary health center between 2002-2021 to contribute for the future genetic counseling of Turkish NSHL patients. Materials and Methods: Two exons of the GJB2 gene were amplified in 402 NSHL patients by two separate PCR reactions and sequenced using the Sanger technique. Results: We found 13 different GJB2 variants in 35% (141/402) of the patients with NSHL. 53.9% were homozygous and 33.3% were compound heterozygous for the most common (59.21%) variant, c.35delG. Approximately 13% of the patients were found to carry the variants in the heterozygous state. The most frequent GJB2 variant c.35delG was followed by c.71G>A (6.38%), c.-23+1G>A (3.54%) and c.233delG (2.48%). We found heterozygous p.Asp50Glu (c.150C>A) alteration in four of eight patients with keratitis, ichthyosis, deafness (KID) and palmoplantar keratoderma (PPK) syndrome. Conclusion: Our results further emphasize the well-known prevalance of the GJB2 c.35delG alteration being the most predominant variant in the Turkish NSHL patients. The high rate of mono-allelic state could be considered as coincidental due to high allelic heterogeneity of NSHL, or possibly suggestive for digenic inheritance.